14 The long-term oncologic outcomes of minimally invasive surgery (robot-assisted/laparoscopic) versus abdominal radical hysterectomy for early-stage cervical cancer patients treated between 2000 and 2017 at the OSLO university hospital. (18th September 2019) - Sert, MB; Dørum, A; Kristensen, G; Davidson, B; Dahl, A
Abstract : Objectives: To compare the long-term oncologic outcomes after minimally invasive surgery (robot assisted/laparoscopic radical hysterectomy) (MIS) versus abdominal radical hysterectomy (ARH) for early-stage cervical cancer (CC). Methods: This is a large single center retrospective study. From our institution´s patient registry, we identified a total of 587 early-stage cervical cancer patients who underwent either MIS or ARH between 2000 and 2017. We excluded the following patients from the final analysis: (1) received neo-adjuvant treatment prior to surgery; (2) had histologic types other than squamous cell carcinoma, adenocarcinoma, or adenosquamous carcinoma; (3) were double primary cancer cases; (4) had stages higher than stageIB1 (FIGO 2009). We included only patients who underwent radical hysterectomy for early-stage cervical cancer and radical parametriectomy for stumph cancer patients in our study population. Results: In total, 230 and 357 patients were assigned to the MIS and ARH groups, retrospectively. There were no significant differences for any demographics including age, stage, histology. Five-year recurrence free survival was 88.6% (95% CI, 83.4%- 92.3%) and 93.5% (95% CI, 90, 4%- 95.7%), (p=0.04) respectively in the MIS and ARH group, and the five-year cancer specific survival was 95.4% (95% CI, 90.9%- 97.7%) and 97.4% (95% CI, 95.1%- 98.7%), (p=0.12) in the MIS and ARH group, respectively. MIS group have more peritoneal-combined relapses comparing ARH (p=0.02). The relapse rate tended to be highest for squamous cell carcinoma in MIS group (p=0.09). Disease free survival and cancer specific survival were worse in the MIS group p- value= 0.04 and 0.12 respectively. Conclusions: MIS was associated with a higher recurrence rate and mostly of peritoneal-combined type than ARH. MIS tended to have a higher mortality rate than ARH although not statistically significant in patients with early-stage cervical cancer cases.